2020
DOI: 10.1177/0361198120928075
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating Design Guidelines using Mental Workload and Reliability Analysis

Abstract: The generic nature of road design is indiscriminate to age, race, or gender, as it is implicitly assumed that there are few behavioral differences between drivers while traversing various alignment elements (e.g., horizontal curves, tangential segments, etc.). For instance, the perception reaction time required, which is based on an 85th percentile value, on a tangent section is the same as that on a horizontal curve. This suggests that current guidelines do not consider the complexity that some geometric feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 39 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…This result might relate to the increased complexity of the driving situation, as the combination of two aforementioned geometric elements would likely require additional ASD. For example, (Habib et al 2020) examined the credibility of the SSD framework as provided by (Messer 1980) using reliability analysis. The results of reliability analysis, which compared the results of stopping sight distance based on MWL requirements versus the available sight distance, showed the applicability of Messer's framework and its readiness for further applications.…”
Section: Available Sight Distance (Asd)mentioning
confidence: 99%
See 1 more Smart Citation
“…This result might relate to the increased complexity of the driving situation, as the combination of two aforementioned geometric elements would likely require additional ASD. For example, (Habib et al 2020) examined the credibility of the SSD framework as provided by (Messer 1980) using reliability analysis. The results of reliability analysis, which compared the results of stopping sight distance based on MWL requirements versus the available sight distance, showed the applicability of Messer's framework and its readiness for further applications.…”
Section: Available Sight Distance (Asd)mentioning
confidence: 99%
“…Recent literature suggests that there is a link between available sight distance (ASD) and highway safety (Ibrahim et al 2012;Lanzaro et al 2020). For example, (Habib et al 2020) found that the probability of non-compliance dropped from 9.1 % to 0.7% when the MWL for SSD (MWL SSD ) was examined in conjunction with the ASD on horizontal curves. Likewise, a study by (Gargoum et al 2018a) revealed that collision rates increased 2.1-fold among aging drivers most notably on sections of highways with restricted SSDs.…”
Section: Introductionmentioning
confidence: 99%
“…A horizontal or a vertical curve redesign may be considered for highly sharp curves to improve vehicles’ travel speed and reduce delay. This is possible as extracting horizontal or vertical curve parameters is viable using LiDAR data (Gargoum, El‐Basyouny, Shalkamy, & Gouda, 2018; Gouda, El‐Basyouny, & Mello, 2020; Habib, Gouda, & El‐Basyouny, 2020; Habib, Shalkamy, & El‐Basyouny, 2019; Shalkamy & El‐Basyouny, 2020). Using ASD and curve parameters, new requirements for longer ASD can be determined, and a new pavement surface layer can be designed.…”
Section: Possible Countermeasures Policies and Regulationsmentioning
confidence: 99%
“…To determine this, transportation agencies have traditionally needed to manually document roadside clear zone size and slope, and the position of obstructions on a case-bycase basis. Recently, however, because of its millimeterlevel accuracy, reduction in cost, and widespread data collection capabilities, civil engineering research has shifted to the use of lidar as a fast and feasible alternative for data collection (14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%